Exchange-rate volatility and Malaysian-Thai bilateral industry trade flows. Issue 1 (9th January 2017) - Aftab, Muhammad; Syed, Karim Bux Shah; Katper, Naveed Akhter
Abstract : Purpose: After the fall of fix exchange rate regime in early 1970s, the nexus between the exchange rate volatility and trade flows has been of a great interest to the policy makers and researchers. Resultantly an extensive literature is available on the topic. However, the research findings are inconclusiveness so far. The purpose of this paper is to examine the exchange-rate volatility and bilateral industry trade link between the two important countries of Southeast Asia, i.e. Malaysia and Thailand. Design/methodology/approach: This study employs Generalized Autoregressive Conditional Heteroskedasticity (GARCH) (1, 1) to measure exchange rate volatility and autoregressive distributed lag (ARDL) model to study the relationship between exchange rate volatility and trade flows. ARDL approach is suitable to accommodate the mix cases (i.e. stationary and first difference stationary). The paper considers 62 Malaysian exporting and 60 Malaysian importing industries with Thailand over the monthly period 2000-2013. Findings: Findings suggest the influence of exchange-rate volatility on the trade flows in a limited number of industries. Large industries like instruments and apparatus experience negative influence from exchange-rate volatility. Originality/value: Past literature continued to be inconclusiveness on the nexus between exchange-rate volatility and trade flows due to its over-reliance on the aggregated data. Besides, the past studies are more based on quarterly or yearly frequency data. These issues contribute to the aggregation bias. This research focusses on a country bilateral trade pair, using industry level disaggregated monthly data. Such research is rare in Malaysian-Thai bilateral trade context. This study uses a suitable estimation approach and also draws valuable implications.